The prevalence of metabolic syndrome among law enforcement officers who responded to the 9/11 World Trade Center attacks. Issue 9 (September 2016) - Moline, Jacqueline M.; McLaughlin, Mary Ann; Sawit, Simonette T.; Maceda, Cynara; Croft, Lori B.; Goldman, Martin E.; Garcia, Mario J.; Iyengar, Rupa L.; Woodward, Mark
Abstract : Background: Law enforcement officers (LEOs) experience high rates of cardiovascular events compared with the general US population. Metabolic syndrome (MetS) confers an increased risk of cardiovascular disease and all‐cause mortality. Data regarding MetS among LEOs are limited. Methods: We sought to determine the prevalence of MetS and its associated risk factors as well as gender differences among LEOs who participated in the World Trade Center (WTC) Law Enforcement Cardiovascular Screening (LECS) Program from 2008 to 2010. We evaluated a total of 2, 497 participants, 40 years and older, who responded to the 9/11 WTC attacks. Results: The prevalence of MetS was 27%, with abdominal obesity and hypertension being the most frequently occurring risk factors. MetS and its risk factors were significantly higher among male compared to female LEOs, except for reduced HDL‐cholesterol levels. Conclusions: MetS is a rising epidemic in the United States, and importantly, approximately one in four LEOs who worked at the WTC site after 9/11 are affected. Am. J. Ind. Med. 59:752–760, 2016. © 2016 Wiley Periodicals, Inc.